Tài liệu hướng dẫn cho các doanh nghiệp nhỏ và vừa = Getting started in export : A training manual for SMEs (Hà Nội, 1998)
Practical, factual and easy to read, this fully updated edition seeks to provide all the information necessary to make a good start in exporting. Packed with details of all the latest legislation and market developments, it will guide you through the process of exporting from researching overseas markets to delivering the goods and getting paid.
Keywords: Export marketing,Small business,Foreign trade promotion,Phát triển thương mại quốc tế,Tiếp thị xuất khẩu,Doanh nghiệp nhỏ; Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Sổ tay, sách hướng dẫn,Sổ tay, sách hướng dẫn,Sổ tay, sách hướng dẫn; Developing countries,Developing countries,Developing countries,Nước đang phát triển,Nước đang phát triển,Nước đang phát triển